N-(p-Methoxybenzoyl)-N′-(o-methoxyphenyl)-thiourea - Ali, Hapipah Mohd; Yamin, B.M.; Yusof, M.S.; Khamis, N.A.; Halim, S.N.A. (International Union of Crystallography, 2004)
In the title compound, C16H16N2O 3S, the o-methoxyphenyl and p-methoxybenzoyl groups are cis and trans, respectively, with respect to the S atom across the C-N bonds. The dihedral angle between the central NCSN thiourea fragment and the o-methoxyphenyl group is 63.66 (8)°, while that with the p-methoxybenzoyl group is 40.30 (7)°. The molecules are stabilized by N-H⋯S and C-H⋯O intermolecular hydrogen-bonding interactions, forming zigzag polymeric chains along the a axis. © 2004 International Union of Crystallography Printed in Great Britain - all rights reserved.